sebuah UPAYA IBU HAMIL DALAM MENCEGAH BAYI BERAT LAHIR RENDAH DI WILAYAH UPTD KESEHATAN KECAMATAN SUKOREJO - Sunarti Sunarti (Jurnal Keperawatan Malang, 2019)
Backgraund: One of the factors that influence the risk of infant mortality is a baby with low birth weight. Therefore, health care efforts for pregnancy should be considered to prepare healthy generations and reduce infant mortality. Aim : The purpose of this study is to describe the efforts of pregnant women to prevent LBW. This research use descriptive case studies me. Method: Participants were taken as many as 15 pregnant women. Collecting data using questionnaires 15 questions. The time of data collection is carried out on 10 April - 2 May 2019. Place of research at Puskesmas Sukorejo. Results: The results of the study describe the efforts of pregnant women in preventing LBW in a good category with a percentage of 73.3% and 26.7% in the adequate category. Conclusion :It is hoped that through this study pregnant women can realize the importance of maintaining pregnancy health to prevent LBW and all relevant agencies can help improve the health of pregnant women by holding various counseling or activities to prevent LBW.